Bactericidal efficiency and photochemical mechanisms of micro/nano bubble–enhanced visible light photocatalytic water disinfection. (15th September 2021) - Fan, Wei; Cui, Jingyu; Li, Qi; Huo, Yang; Xiao, Dan; Yang, Xia; Yu, Hongbin; Wang, Chunliang; Jarvis, Peter; Lyu, Tao; Huo, Mingxin
Highlights: Micro/nanobubbles (MNB) promote the photocatalytic disinfection of microbial spores. H2 O2 and OH are the primary active species responsible for the spore inactivation. MNB induced light scattering significantly increases the bactericidal efficiency. Sustainable O2 supply from MNBs can accelerate the hole oxidation of the catalyst. MNB triggered interfacial photoelectric effect plays a key role in the enhancement. Abstract: Microbial contamination of water in the form of highly-resistant bacterial spores can cause a long-term risk of waterborne disease. Advanced photocatalysis has become an effective approach to inactivate bacterial spores due to its potential for efficient solar energy conversion alongside reduced formation of disinfection by-products. However, the overall efficiency of the process still requires significant improvements. Here, we proposed and evaluated a novel visible light photocatalytic water disinfection technology by its close coupling with micro/nano bubbles (MNBs). The inactivation rate constant of Bacillus subtilis spores reached 1.28 h −1, which was 5.6 times higher than that observed for treatment without MNBs. The superior performance for the progressive destruction of spores' cells during the treatment was confirmed by transmission electron microscopy ( TEM) and excitation-emission matrix (EEM) spectra determination. Experiments using scavengers of reactive oxygen species (ROSs) revealed that H2 O2 and OH were the primary active species responsible for the inactivation of spores. The effective supply of oxygen from air MNBs helped accelerate the hole oxidation of H2 O2 on the photocatalyst (i.e. Ag/TiO2 ). In addition, the interfacial photoelectric effect from the MNBs was also confirmed to contribute to the spore inactivation. Specifically, MNBs induced strong light scattering, consequently increasing the optical path length in the photocatalysis medium by 54.8% at 700nm and enhancing light adsorption of the photocatalyst. The non-uniformities in dielectricity led to a high-degree of heterogeneity of the electric field, which triggered the formation of a region of enhanced light intensity which ultimately promoted the photocatalytic reaction. Overall, this study provided new insights on the mechanisms of photocatalysis coupled with MNB technology for advanced water treatment. Graphical abstract: Image, graphical abstract